ANALYSIS OF CONSUMER PREFERENCES FOR TEMPE PRODUCT ATTRIBUTES IN FAKFAK REGENCY - Novita Fransisca (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
Consumer preference refers to the level of importance or degree of liking that consumers assign to a product they intend to purchase or consume. Product attributes, including taste, price, and size, are key factors influencing purchasing decisions. The problem addressed in this study is identifying which product attributes significantly influence consumers' purchase intentions. This study aims to determine the product attributes that influence the purchasing decisions of the people of Fakfak and to analyze their preferences for tempe products. The research was conducted at Tanjung Wagom Market in Fakfak Regency, West Papua, Indonesia. A quantitative research approach was employed. The study population consisted of the residents of Fakfak Regency, and data were collected from 30 respondents through a survey. The sample comprised 30 respondents selected using the accidental sampling technique. The analytical methods used in this study were conjoint analysis and the Likert scale. The results indicate that the product attribute with the highest utility value is taste, specifically the savory level, with a utility value of 1.041. The second highest-ranked attribute is price, at IDR 5,000, with a utility value of 0.274, while the third is size, with the large size level having a utility value of 0.307. The importance value analysis shows that the taste attribute is the most influential factor, accounting for 54.469% of consumer preferences.